Homogeneous and ultrasensitive detection of telomerase activity via gold nanorod-based fluorescence resonance energy transfer. Issue 21 (1st September 2016) - Wang, Yanjun; Yang, Luzhu; Li, Baoxin; Jin, Yan
Abstract : A homogeneous and PCR-free fluorescent strategy has been developed for sensitively and specifically studying telomerase activity and inhibition via GNR-based fluorescence resonance energy transfer. Abstract : As a universal biomarker, telomerase is one of the promising targets for cancer diagnosis and therapy. Therefore, it is meaningful to develop facile, robust and sensitive methods for evaluation of telomerase activity. Herein, combined with fluorescence resonance energy transfer (FRET), we creatively designed a gold nanorod (GNR)-based FRET method to detect telomerase activity from cell extracts. As the signal probe, carboxyfluorescein-modified DNA probes (F-DNA) hold negative electricity. The electrostatic interaction between F-DNA and positively charged GNRs makes F-DNA close to GNRs, which leads to weak FRET between the F-DNA and GNRs. In the presence of telomerase, a telomerase substrate (TS) primer was elongated to form a long single-stranded DNA, which could hybridize with numerous F-DNA to form long dsDNAs. The strengthened electrostatic interaction leads to a more efficient FRET between GNRs and dsDNA. Therefore, the amplified fluorescence quenching efficiency can greatly improve the sensitivity. The telomerase activity in the HeLa extracts equivalent to 1 cell was detected sensitively without the polymerase chain reaction (PCR) amplification and enzyme auxiliary signal amplification. Moreover, this facile protocol can be used to distinguish tumor cells from normal cells and study the inhibition effect of telomerase inhibitors, which shows its potential application value in clinical diagnosis and drug screening.